Pengaruh Management Change, Ukuran Perusahaan Klien, Dan Audit Fee Terhadap Auditor Switching - Vivi Aulia Najwa; Efrizal Syofyan (Universitas Negeri Padang, 2020)
The purpose of this study was to analyze the effect of management change, client company size, audit fee on auditor switching. The data used in this study are annual and financial reports In manufacturing companies listed on the indonesia stock exchange (idx) in the period 2014-2018. The method of taking data samples using purposive sampling method. Based on certain criteria. Based on the retrieval method obtained A sample of 136 companies. Hypothesis testing in this study uses Logistic regression analysis. The results show that management change, company size has no effect on auditor switching and audit fees have a positive effect on auditor switching